Methodological Aspects Regarding the Planning and Development of Integrated Tourist Routes and Circuits. Case Study: Luncasprie, Romania - Grigore Vasile HERMAN; Lucian BLAGA (Editura Universităţii din Oradea, 2022)
The intensification of tourist activities at the level of the Bihor Tourist Destination, in parallel with the increase in the need to diversify the local tourist offer, led to the need to identify new solutions in this regard. Due to the geographical location of the studied area, in the immediate vicinity of the Oradea Municipality, this space, due to the values with which it is endowed with the natural environment and the existing tourist infrastructure, can be constituted as a viable alternative with a role in reducing the tourist pressure in the Oradea area and in diversifying the tourist offer through rural tourism and agritourism. In this context, the present study aims to propose integrated tourist routes and circuits following the analysis of the local tourist potential. The results obtained consisted in carrying out an analysis of the natural environment from a tourism perspective and making some development proposals (three routes and a tourist circuit).